A portrait of Mendelssohn - Brown, Clive, 1947- (Yale University Press, 2003)
Rejecting the received view of Mendelssohn as a lightweight this work draws on extensive documentary records to demonstrate that he was in fact an innovative & highly cerebral composer who has had a considerable influence on musical thought into the 20th century.